Augmented reality, virtual reality, and computer graphics : 7th International Conference, AVR 2020, Lecce, Italy, September 7-10, 2020, proceedings, part II /: 7th International Conference, AVR 2020, Lecce, Italy, September 7-10, 2020, proceedings, part II. ([2020]) - Unknown
No abstract available